Agriculture and nutrition in China - Chen, Kevin Z.; Wang, Zimeiyi (International Food Policy Research Institute, 2019)
This chapter discusses the linkages between agriculture, food, and nutrition in China. It begins with an overview of existing nutrition governance and policies, followed by a discussion of the major research progress on agriculture and nutrition links in recent years. The chapter then identifies gaps in current agriculture and nutrition policies, and provides policy perspectives on improving the agricultural sector for improving nutrition in China.